2009
DOI: 10.1007/s10653-009-9262-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of oily sludge-contaminated soil by stimulating indigenous microbes

Abstract: In situ bioremediation of oily sludge-contaminated soil by biostimulation of indigenous microbes through adding manure was conducted at the Shengli oilfield in northern China. After bioremediation for 360 days, total petroleum hydrocarbon (TPH) content was reduced by 58.2% in the treated plots compared with only 15.6% in the control plot. Moreover, bioremediation significantly improved the physicochemical properties of the soil in the treated plot. Soil microbial counts and community-level physiological profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(84 citation statements)
references
References 19 publications
5
72
3
2
Order By: Relevance
“…Toxicity levels of the treated wastewater must be below a permissible levels and pose no risk to public health and the environment (Liu et al, 2010;Melo et al, 2013). Fig.…”
Section: Ecotoxicological Analysismentioning
confidence: 99%
“…Toxicity levels of the treated wastewater must be below a permissible levels and pose no risk to public health and the environment (Liu et al, 2010;Melo et al, 2013). Fig.…”
Section: Ecotoxicological Analysismentioning
confidence: 99%
“…Investigations have demonstrated that bioremediation is a feasible solution for treating organic contaminants including PCB, PCNB, DDT, DDE and DDD (Fang et al, 2010;Li and Yang, 2013;Liu et al, 2010;Wang et al, 2016a). High efficiency degradation strains are a key factor for bioremediation of organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, most refineries treat oil sludge using conventional methods which includes; physical treatment (storage, landfilling, combustion and incineration in a rotary kiln, lime stabilization, stabilization and solidification) (Wright and Noordhius, 1991;Karamalidis and Voudrias, 2001;Bhattacharyy and Shekdar, 2003;Radetski et al, 2006;Beech et al, 2009;Liu et al, 2010), chemical treatment (oxidative thermal treatment, treatment with fly-ash, pyrolysis treatment and solvent extraction) (Bonnier et al, 1980;Atlas, 1984;Taiwo and Otolorin, 2009) and biological treatment (landfarming, bio-reactor treatment and composting) (Pereira-Neta, 1987;Piotrowski, 1991;Lees, 1996;Singh et al, 2001;Hejazi et al, 2003;Mahmoud, 2004;De-qing et al, 2007;Srinivasarao et al, 2011;Udotong et al, 2011;Besalatpour et al, 2011). Most of the physical and chemical methods require expensive equipments and high energy to treat the oil sludge.…”
Section: Treatment Technologies and Disposal Of Oil Sludgementioning
confidence: 99%
“…Some of these methods convert oil sludge into lighter products and reduce the quantity before disposal. Some of the methods may generate by-products that may need to be treated using other methods before disposal to a landfill (Liu et al, 2010), making them more expensive. Exam-ples of the conventional methods used are discussed below.…”
Section: Treatment Technologies and Disposal Of Oil Sludgementioning
confidence: 99%
See 1 more Smart Citation